Ze studiów nad najstarszym osadnictwem wczesnośredniowiecznym na Pomorzu Zachodnim - Machajewski, Henryk (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
The issue of the earliest medieval settlement in West Pomerania continues to generate discussions in the context of its dating and spread to various regions. The latest growth in the number of new archaeological sources related to this issue necessitates a new approach to the process of formation thereof. An attempt at explaining the chronological relations of this settlement in the face of the latest ancient settlement is a separate issue.